PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PROTOKOL KESEHATAN DI KAMPUS UNIVERSITAS RIAU - Saras, Siti; Hambali, Hambali; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by a lack of awareness of health protocols during the Covid-19 pandemic. The formulation of the problem in this study is how the Riau University students' perceptions of the Riau University campus health protocol. The purpose of this study was to determine the perceptions of Riau University students towards the health protocol at the Riau University campus. Researchers used quantitative descriptive methods, data collection instruments used in this study were a questionnaire or a questionnaire consisting of 15 questions. The population in this study were students of the University of Riau. Sampling using purposive sampling technique. Based on the results of research on Riau University students' perceptions of health protocols on the Riau University campus, it can be concluded that: Regulation of the Minister of Health on Health Protocols of the Republic of Indonesia, 2020. Guidelines for the Prevention and Control of Coronavirus Disease Covid-19 are in the Good category. This is because the result of the answer is Always (SL) plus Frequently (SR), namely 36.81% + 28.36% = 65.17%. Thus, it can be concluded that the Regulation of the Minister of Health regarding Health Protocols of the Republic of Indonesia, 2020. Guidelines for the Prevention and Control of Coronavirus Disease Covid-19 are at a Good level. Pekanbaru Mayor Regulation Number 104 Year 2020 Concerning New Guidelines for Productive and Safe Living Conduct in the Prevention and Control of Coronavirus Disease (COVID-19) in Pekanbaru City is in the Very Good category This is because the results of the answers are Always (SL) plus Frequently (SR) namely 61.5% + 35% = 96.5%. Thus, it can be concluded that Pekanbaru Mayor Regulation Number 104 Year 2020 Concerning Guidelines for Productive and Safe Community New Life Behavior in the Prevention and Control of Corona Virus Disease 2019 (COVID-19) in Pekanbaru City is at a Very Good level.Key Words: Perception, Student, Health Protocol